Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's solve the given problem step-by-step.
We are given the function [tex]\( f(x) = x^2 + 3x + 5 \)[/tex] and we are asked to find [tex]\( f(3+h) \)[/tex].
1. Substitute [tex]\( x \)[/tex] with [tex]\( 3+h \)[/tex] in the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3+h) = (3+h)^2 + 3(3+h) + 5 \][/tex]
2. Expand the squared term [tex]\((3+h)^2\)[/tex]:
[tex]\[ (3+h)^2 = 3^2 + 2 \cdot 3 \cdot h + h^2 = 9 + 6h + h^2 \][/tex]
3. Distribute and simplify the other term [tex]\( 3(3+h) \)[/tex]:
[tex]\[ 3(3+h) = 3 \cdot 3 + 3 \cdot h = 9 + 3h \][/tex]
4. Substitute back and combine all terms:
[tex]\[ f(3+h) = 9 + 6h + h^2 + 9 + 3h + 5 \][/tex]
5. Add up all like terms:
[tex]\[ h^2 + (6h + 3h) + (9 + 9 + 5) = h^2 + 9h + 23 \][/tex]
Thus, the function [tex]\( f(3+h) \)[/tex] simplifies to:
[tex]\[ f(3+h) = h^2 + 9h + 23 \][/tex]
As per the choices given, the correct answer is:
A. [tex]\( h^2 + 9h + 23 \)[/tex]
We are given the function [tex]\( f(x) = x^2 + 3x + 5 \)[/tex] and we are asked to find [tex]\( f(3+h) \)[/tex].
1. Substitute [tex]\( x \)[/tex] with [tex]\( 3+h \)[/tex] in the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(3+h) = (3+h)^2 + 3(3+h) + 5 \][/tex]
2. Expand the squared term [tex]\((3+h)^2\)[/tex]:
[tex]\[ (3+h)^2 = 3^2 + 2 \cdot 3 \cdot h + h^2 = 9 + 6h + h^2 \][/tex]
3. Distribute and simplify the other term [tex]\( 3(3+h) \)[/tex]:
[tex]\[ 3(3+h) = 3 \cdot 3 + 3 \cdot h = 9 + 3h \][/tex]
4. Substitute back and combine all terms:
[tex]\[ f(3+h) = 9 + 6h + h^2 + 9 + 3h + 5 \][/tex]
5. Add up all like terms:
[tex]\[ h^2 + (6h + 3h) + (9 + 9 + 5) = h^2 + 9h + 23 \][/tex]
Thus, the function [tex]\( f(3+h) \)[/tex] simplifies to:
[tex]\[ f(3+h) = h^2 + 9h + 23 \][/tex]
As per the choices given, the correct answer is:
A. [tex]\( h^2 + 9h + 23 \)[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.